FUNCTIONAL RESILIENCE IN A SOCIAL CONTEXT: GENDER DIFFERENCES IN SOCIAL PROTECTION. (11th November 2018) - Hawkley, L; Wroblewski, Kristen, E
Abstract: Assistance with ADL disabilities reduces risk for depression and mortality, but prior research suggests that the social context in which help is provided may matter. Using data from the National Social Life, Health and Aging Project, we examine how the social relationships of men and women with ADL/IADL limitations affect depressive symptoms and mortality five years later. For disabled women, proportion of kin in the network, but not source of help, is associated with increased mortality (OR=3.55, 95% CI:1.59–7.93). For disabled men, source of help, but not proportion kin, is associated with increased mortality, such that married men reliant on a non-spousal other are at greater risk than men reliant on their spouse (OR=3.42, 95% CI:1.01–11.54). Among married dependent women, strain in the spousal relationship is positively associated and having a child negatively associated with depressive symptoms at follow-up. Functional resilience appears optimized when broader social resources are harnessed.